Neuropeptide W, an endogenous NPBW1 and NPBW2 ligand, produced an analgesic effect via activation of the descending pain modulatory system during a rat formalin test. (February 2021) - Nakamura, Shingo; Nonaka, Takahiro; Yoshida, Koji; Yamada, Toshihiko; Yamamoto, Tatsuo
Neuropeptide W (NPW) messenger ribonucleic acid (mRNA) and NPBW1 and/or NPBW2 mRNA are expressed in the descending pain inhibitory system. In the present study, we examined whether NPW microinjected into the descending pain inhibitory system, such as the periaqueductal gray (PAG), locus coeruleus (LC), and rostral ventromedial medulla (RVM), produces an analgesic effect using a rat formalin test. Microinjections of NPW into the PAG ipsilateral and contralateral to the formalin-injected side, LC ipsilateral and contralateral to the formalin-injected side, and RVM produced an analgesic effect. In the RVM study, the analgesic effect was antagonized by WAY100135, a 5-HT1A antagonist, and enhanced by prazosin, an α1 antagonist, and SB269970, a 5-HT7 antagonist. Naloxone, an opioid antagonist, also antagonized the effect of NPW in the RVM study. In the ipsilateral LC study, the analgesic effect was antagonized by WAY100135, idazoxan, an α2 antagonist, and naloxone and was enhanced by prazosin and SB269970. In the contralateral LC study, the analgesic effect was antagonized by prazosin, idazoxan, SB269970, and naloxone. The analgesic effect was antagonized by WAY100135, SB269970, idazoxan, and naloxone in the ipsilateral and contralateral PAG studies. These findings strongly suggest that NPBW1/W2 activation by NPW microinjection into the RVM, LC, and PAG affect the descending pain modulatory system and produce anti-nociceptive and pro-nociceptive effects in the rat formalin test.